Doctor Who. The celestial toymaker [videorecording (Blu-Ray)]. (BBC, 2024)
The travelers arrive in a strange domain presided over by the Celestial Toymaker, an enigmatic, immortal entity who forces them to play a series of games, failure at which will render them his playthings for all eternity.